DEMOKRASI DIGITAL SEBUAH TREN BARU GLOBALISASI SOSIAL BUDAYA DI INDONESIA - Hartanto . (Jurnal Ilmu dan Budaya, 2016)
Globalization is an expansion, deepening, and acceleration which connect to all aspects of socio-contemporary life around the world. Globalization promotes the development of digital democracy in Indonesia in the form of public sphere channels through cyberspace characterrized by the expansion of global communication and the widespread of institutions and democratic norms demands. Digital democracy brings impact to the emergence of public sphere which becomes the mediation between society and government where the puclic can manage and organize independently as the owners of public opinion in function to advocate and control the government policy through public spheres; one of them is through Change.Org.